Pengaruh Penilaian Prestasi Kerja Terhadap Produktivitas Kerja Karyawan: Studi Kasus Pada Karyawan PT. Bank BTPN Tbk. Cabang Tebing Tinggi - Syafrizal, Rodi (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This research was conducted to determine the extent to which work performance appraisals influence employee work productivity at Bank BTPN, Tbk, Tebing Tinggi Branch. This type of research uses a quantitative approach method with a sample of 35 respondents who were determined based on a saturated sampling technique. With simple linear regression analysis, in SPSS version 25.0. Based on the results of this analysis, it can be concluded that the assessment of work performance has a positive and significant effect on the work productivity of Bank BTPN Tebing Tinggi Branch employees.